ONE-DIMENSIONAL BOUNDARY FIELD PROBLEM ANALYTIC SOLUTION REALIZATION USING MATLAB AND .NET C# ENVIRONMENT - Judovičs, Edgars; Platonovs, Valdis; Kangro, Ilmārs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Three-dimensional boundary problem for differential equation can help solve many interesting cases. But usually 3-D method is not needed, so there is a need to convert it to a one-dimensional variant. Also a very good thing is that the solution is very accurate, when using a computer. In this paper, the authors tried to make a solution in MATLAB with using C# programming language to make possible many entries.